Scopolamine Administration Modulates Muscarinic, Nicotinic and NMDA Receptor Systems - Falsafi, Soheil Keihan (Public Library of Science, 2012)
Studies on the effect of scopolamine on memory are abundant but so far only regulation of the muscarinic receptor (M1) has been reported. We hypothesized that levels of other cholinergic brain receptors as the nicotinic receptors and the N-methyl-D-aspartate (NMDA) receptor, known to be involved in memory formation, would be modified by scopolamine administration. C57BL/6J mice were used for the experiments and divided into four groups. Two groups were given scopolamine 1 mg/kg i.p. (the first group was trained and the second group untrained) in the multiple T-maze (MTM), a paradigm for evaluation of spatial memory. Likewise, vehicle-treated mice were trained or untrained thus serving as controls. Hippocampal levels of M1, nicotinic receptor alpha 4 (Nic4) and 7 (Nic7) and subunit NR1containing complexes were determined by immunoblotting on blue native gel electrophoresis. Vehicle-treated trained mice learned the task and showed memory retrieval on day 8, while scopolamine-treatment led to significant impairment of performance in the MTM. At the day of retrieval, hippocampal levels for M1, Nic7 and NR1 were higher in the scopolamine treated groups than in vehicle-treated groups. The concerted action, i.e. the pattern of four brain receptor complexes regulated by the anticholinergic compound scopolamine, is shown. Insight into probable action mechanisms of scopolamine at the brain receptor complex level in the hippocampus is provided. Scopolamine treatment is a standard approach to test cognitive enhancers and other psychoactive compounds in pharmacological studies and therefore knowledge on mechanisms is of pivotal interest.